From home to campus: The homesickness and adaptation experience of migrant students - Ica Purnama; Vika Rahmawati; Dira Okta Saraswati; Melysah Ramadona; Lentera Langit; Ghina Reftantia; Vieronica Varbi Sununianti; Elita Aidillah (Priviet Social Sciences Journal, 2026)
Educational mobility encourages many students to leave their home areas to continue their studies in higher education. The move not only presents academic opportunities but also poses various social and emotional challenges, one of which is homesickness. This study aims to analyze the experiences of homesickness and social adaptation among migrant students at Sriwijaya University, Indralaya Campus. The research uses a qualitative approach with phenomenological methods. The data were obtained through in-depth interviews with five migrant students who were selected purposively based on their experience of living far from their families and having experienced homesickness. Data was analyzed using an interactive model through the stages of data reduction, data presentation, and a conclusion drawn. The results of the study showed that homesickness is experienced in the form of longing for family, feelings of loneliness due to the loss of a familiar social environment, culture shock when entering a new environment, and difficulty living life independently. This experience is part of the social adaptation process that takes place when students enter a social environment that is different from their home region. Adaptation is carried out through changes in daily behavior, the development of new social relationships, involvement in student organizations, and the process of forming an identity as a more independent individual. The findings of the study show that homesickness is not only an emotional response to separation from home but also an important part of the process of social adjustment and maturation of migrant students.